Efforts To Improve Early Detection of Diabetes Mellitus in UPTD Puskesmas Ngasem Kediri District - Prasetyo, Joko; Sulistyowati, Titis; Fatah, Nur Alim; Rachmatulaili; Hidayat, Ichwan (Universitas STRADA Indonesia, 2025)
Diabetes mellitus (DM) is a chronic disease with a steadily increasing global prevalence and is among the leading causes of morbidity and mortality, including in Indonesia. This condition creates a major health and economic burden, particularly for individuals with low to middle socioeconomic status, as it is often detected late and inadequately treated. Limited public awareness of early symptoms, modifiable risk factors, and preventive measures is a key factor contributing to delayed diagnosis and the risk of serious complications in the future. This community service program was carried out at Ngasem Community Health Center, Kediri Regency, and involved 25 participants with a history of DM. The primary objective was to enhance community knowledge and awareness regarding DM through health education using a participatory approach. Knowledge levels were assessed before and after the intervention to evaluate the effectiveness of the educational activity. The results indicated a clear improvement in participants’ understanding of the early symptoms of DM, associated risk factors, and preventive strategies. This suggests that participatory health education is an effective approach to improving public knowledge and encouraging proactive health behavior. Sustained and systematic educational interventions are therefore essential to support the prevention and control of DM at the community level.